Simulation of Flexural and Tensile Properties of Additively Manufactured Continuous Carbone Fiber - Sarkon, Garshasp Keyvan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
The act of additive manufacturing (AM) entails layer by layer creation of a layered structure from the ground up. This competence allows for a sophisticated design to be carried out with geometries that are sometimes impossible to achieve and materialize with conventional manufacturing methods such as subtractive manufacturing, molding, foaming, etc. Fused filament fabrication (FFF) or sometimes addressed as fused deposition modeling (FDM) is among the AM methods which couples well with manufacturing composite materials. Fabricated composite materials using FFF has proven to be particularly useful in a plethora of industries, namely in the aerospace and aeronautics, automotive industry, therapeutic apparatuses, and sports goods. In general, invented parts with FFF method have excellent mechanical properties which make them worthy of further study. Performance under tensile tension and flexural (bending) tensions are particularly significant in composite materials. Therefore, a thorough finite element modeling (FEM) on tensile and flexural behavior of FFF fabricated continuous carbon fiber specimen in the COMSOL multi-physics® environment is executed while using layered shell elements to express the properties in a layered structure. The results gathered from the FEM was compared to other experimental and related empirical studies. Furthermore, the type of effects a composite material might have on tensile properties such as infill ratio, infill pattern, fiber content, layer orientation and stacking sequence will be put under scope. Based on the results provided under this new study, the tensile and flexural simulated specimen shown better maximum tensile and flexural capabilities, with 1490 [MPa] and 1240 [MPa] Max stress, while the tensile model underwent the boundary load of 559.9 MPa and the flexural model went through 302.70 N at two points to simulate the two-point flexure test.

ÖZ: Eklemeli imalat (AM) uygulaması, bir numunenin sıfırdan katman katman oluşturulmasını gerektirir. Bu yetenek, diğer geleneksel üretim yöntemleriyle bazen oluşturulması imkansız olan geometrilerle karmaşık bir tasarımın gerçekleştirilmesine olanak tanır. Erimiş filament üretimi (FFF), kompozit malzemelerle iyi eşleşen AM yöntemleri arasındadır. FFF kullanan fabrikasyon kompozit malzemelerin, otomotiv endüstrisi, havacılık, tıbbi cihazlar ve spor ürünleri gibi sayısız endüstride özellikle yararlı olduğu kanıtlanmıştır. Genel olarak, FFF yöntemiyle üretilmiş parçalar, onları daha fazla çalışmaya değer kılan mükemmel mekanik özelliklere sahiptir. Gerilim altındaki davranış ve eğilme gerilimleri kompozit malzemelerde özellikle önemlidir. Bu nedenle, COMSOL çoklu fizik ortamında FFF ile üretilmiş sürekli karbon fiber numunenin çekme ve eğilme davranışı üzerine kapsamlı bir sonlu eleman modellemesi (FEM), katmanlı bir yapıdaki özellikleri ifade etmek için katmanlı kabuk elemanları kullanılırken gerçekleştirilir. FEM'den elde edilen sonuçlar, diğer deneysel ve ilgili ampirik çalışmalarla karşılaştırıldı. Ayrıca, dolgu oranı ve deseni, lif içeriği, katman yönelimi ve istifleme sırası gibi bir kompozit malzemenin çekme özellikleri üzerindeki etkilerinin türü de kapsam altına alınacaktır. Bu yeni çalışma kapsamında sağlanan sonuçlara dayanarak, çekme modeli 559.9 MPa sınır yüküne maruz kalırken, çekme ve eğilme simülasyonu numunesi, 1238 [MPa] ve 1652 [MPa] Maks stres ile daha iyi maksimum çekme ve eğilme yetenekleri gösterdi. eğilme modeli, iki nokta eğilme testini simüle etmek için iki noktada 302,70 N'den geçti.
Master of Science in Mechanical Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2022. Co-Supervisor: Qasim Zeeshan and Supervisor: Asst. Prof. Dr. Babak Safaei
Keywords: Mechanical Engineering; Additive manufacturing; Three-dimensional printing; Manufacturing processes; Tensile and Flexural Properties, 3D Printing, Fused Filament Fabrication, Finite Element Modeling, Carbon Fiber Composites